Pengaruh Struktur Aktiva, Ukuran Perusahaan, Pertumbuhan Penjualan, dan Kepemilikan Institusional Terhadap Struktur Modal Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2019 - Panjaitan, Renta Ulima; Hidayat, Taufik (Asosiasi Dosen Akuntansi Indonesia, 2024)
The purpose of this study is to determine the effect of asset structure, firm size, sales growth and institutional ownership on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2019. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2019, which are 167 companies. The sampling method used in this research is the purposive sampling method, with a total sample of 38 companies. The research period is 2 years, 2018 to 2019, so the research data is 76 companies. The data analysis technique used in this study consisted of descriptive statistical analysis, classical assumption test, multiple linear regression and hypothesis testing. The results of this study empirical evidence that the asset structure and firm size have not affected capital structure, sales growth affects capital structure, while institutional ownership has no effect on capital structure